Experimental Investigation on Heat Transfer Performance of a Compact Heat Exchanger with Spray Cooling - Song Xia; Wang Jiawei; Shi Junye; Chen Jiangping (Zhileng xuebao)
To investigate the effects of spray cooling on air-side heat transfer and pressure drop, and to determine the water spray flow rate when spray droplets evaporate completely on the hot surface of a compact heat exchanger, we built an experimental plant to analyze the air-side heat transfer and pressure drop of an automotive compact heat exchanger with and without spray cooling. The results indicate that the j factor and f factor obtained from experiments without spray were in good agreement with those calculated from Chang’s correlations, within an error of 10%. Compared with that without spray, the j factor with spray increased significantly, but the increasing rate declined with a decrease in the spray flow rate and substrate temperature. The f factor with spray changed slightly compared with that without spray. Using the substrate temperature and air velocity as variables, we proposed a correlation of the critical value of the spray flow rate (where spray droplets can evaporate completely). Based on Chang’s correlation, the j factor with spray can be obtained using a correction factor. These results support the prediction of air-side heat transfer with spray and also facilitate future application of spray cooling in automotive air conditioners.